2006
DOI: 10.2208/jsceja.62.595
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Deterioration of High Damping Rubber Bridge Bearing

Abstract: In recent years, high damping rubber (HDR) bridge bearings have become widely used because of the excellent ability to provide high damping as well as flexibility. However, there are few systematic studies on the deterioration problems of HDRs during their service life, and usually the long-term performance was not considered in the design stage. In this research, through accelerated thermal oxidation tests on HDR blocks, the property variations inside the HDR bridge bearing are examined. A deterioration predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It starts from the surface and makes the rubber stiff and brittle and resulting in higher hardness, lower tensile strength, and shorter elongation. Itoh et al 8) , defined two regions of rubber from the used bridge bearing: outer and inner, and reported that the property in the outer region deteriorates but does not extend to the inner region. The thickness of the outer region is called the critical depth: dc which is proportional to the exponent of reciprocal of temperature as shown in equation (7): In Fig.6, the critical depth is approximatly 70mm from both the outer and inner surface of the body.…”
Section: (1) Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It starts from the surface and makes the rubber stiff and brittle and resulting in higher hardness, lower tensile strength, and shorter elongation. Itoh et al 8) , defined two regions of rubber from the used bridge bearing: outer and inner, and reported that the property in the outer region deteriorates but does not extend to the inner region. The thickness of the outer region is called the critical depth: dc which is proportional to the exponent of reciprocal of temperature as shown in equation (7): In Fig.6, the critical depth is approximatly 70mm from both the outer and inner surface of the body.…”
Section: (1) Test Proceduresmentioning
confidence: 99%
“…The difference in average temperature between the north area and FD No.3 in the south island is about 15°C 3) which might be the reason for this difference in elongation coefficient. The calculated critical depths by Itoh et al 8) at each site location are shown in Fig.9. They look close to the measured distribution of FD No.8, 9, 10, and 11 (from 55 to 74mm ) in Fig.9 except for the 3000H-14 years in the north area where the critical depth is 102mm.…”
Section: (1) Test Proceduresmentioning
confidence: 99%
“…The mechanical properties of the HDRBs change uniformly along the radial direction of the isolator in a relatively short time, until a stable equilibrium state is reached in the inner region bounded by an external critical depth, 5 the latter being an exponential function of the temperature. 6 The outer region is also affected by an oxidation process, related to time and depending on the amount of oxygen, which produces a degradation of properties whose effects diminish moving towards the critical depth. Moreover, the HDRBs considerably increase their horizontal and vertical stiffnesses for decreasing values of the air temperature through rubber crystallization due to prolonged exposure to cold weather, whereas their cyclic behaviour does not change significantly at high air temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…During the lifetime of the elastomeric (e.g., high‐damping rubber bearings [HDRBs]) and sliding (e.g., flat sliding bearings [FSBs]) bearings, representing some of the most widely used types of isolation systems, ageing and air temperature are important factors that affect the degradation of rubber and friction coefficient of the sliding surface, respectively. The mechanical properties of the HDRBs change uniformly along the radial direction of the isolator in a relatively short time, until a stable equilibrium state is reached in the inner region bounded by an external critical depth, the latter being an exponential function of the temperature . The outer region is also affected by an oxidation process, related to time and depending on the amount of oxygen, which produces a degradation of properties whose effects diminish moving towards the critical depth.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the HDRBs change uniformly along the radial direction of the isolator in a relatively short time, until a stable equilibrium state is reached in the inner region bounded by an external critical depth [4], the latter being an exponential function of the temperature [5]. The outer region is also affected by an oxidation process, related to time and depending on the amount of oxygen, which produces a degradation of properties whose effects diminish moving towards the critical depth.…”
Section: Introductionmentioning
confidence: 99%